Intronic Polymorphisms Affecting Alternative Splicing of Human Dopamine D2 Receptor Are Associated with Cocaine Abuse - Moyer, Robert A; Wang, Danxin; Papp, Audrey C; Smith, Ryan M; Duque, Linda; Mash, Deborah C; Sadee, Wolfgang (Neuropsychopharmacology (New York, N.Y.), 2011)
The dopamine receptor D2 (encoded by DRD2 ) is implicated in susceptibility to mental disorders and cocaine abuse, but mechanisms responsible for this relationship remain uncertain. DRD2 mRNA exists in two main splice isoforms with distinct functions: D2 long (D2L) and D2 short (D2S, lacking exon 6), expressed mainly postsynaptically and presynaptically, respectively. Two intronic single-nucleotide polymorphisms (SNPs rs2283265 (intron 5) and rs1076560 (intron 6)) in high linkage disequilibrium (LD) with each other have been reported to alter D2S/D2L splicing and several behavioral traits in human subjects, such as memory processing. To assess the role of DRD2 variants in cocaine abuse, we measured levels of D2S and D2L mRNA in human brain autopsy tissues (prefrontal cortex and putamen) obtained from cocaine abusers and controls, and genotyped a panel of DRD2 SNPs (119 abusers and 95 controls). Robust effects of rs2283265 and rs1076560 on reducing formation of D2S relative to D2L were confirmed. The minor alleles of rs2283265/rs1076560 were considerably more frequent in Caucasians (18%) compared with African Americans (7%). Also, in Caucasians, rs2283265/rs1076560 minor alleles were significantly overrepresented in cocaine abusers compared with controls (rs2283265: 25 to 9%, respectively; p =0.001; OR=3.4 (1.7–7.1)). Several SNPs previously implicated in diverse clinical association studies are in high LD with rs2283265/rs1076560 and could have served as surrogate markers. Our results confirm the role of rs2283265/rs1076560 in D2 alternative splicing and support a strong role in susceptibility to cocaine abuse.